2022
DOI: 10.1111/cars.12391
|View full text |Cite
|
Sign up to set email alerts
|

The extreme gendering of COVID−19: Household tasks and division of labour satisfaction during the pandemic

Abstract: For many years, scholars have directed our attention to the gender gap in domestic labour. Even when women engage in paid employment, they nevertheless perform the majority of the household labour in most wealthy countries. At the same time, disasters and crises both expose and exacerbate existing social inequalities. In this paper, we ask: in what ways has the COVID−19 pandemic contributed to the gender gap in household labour, including childcare? How do women and men feel about this gap? Using data from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…Additionally, research demonstrated that men also perceived an increase in their domestic workload, however, this extra work is considered a slight increase [37,38] and lower than what women do [39,40]. Some research has indicated that the pandemic could produce "regressive shifts in gender role attitudes" (p. 30) [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, research demonstrated that men also perceived an increase in their domestic workload, however, this extra work is considered a slight increase [37,38] and lower than what women do [39,40]. Some research has indicated that the pandemic could produce "regressive shifts in gender role attitudes" (p. 30) [41].…”
Section: Discussionmentioning
confidence: 99%
“…The median women's age was 36 years (IQR: [31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Almost half of the women (47.5%) had completed college studies, while 2.8%had an incomplete or complete high school education.…”
Section: General Sample Characteristicsmentioning
confidence: 99%
“…As critical infrastructure, like childcare centers and schools, closed because of COVIDrelated restrictions, parents were forced to simultaneously juggle increased caregiving and new homeschooling responsibilities along with their full-time careers (Collins et al 2021;Lee and Parolin 2021). Several studies document a marked increase in the gender gap in housework and childcare during the pandemic (Abromaviciute and Carian 2022;Haney and Barber 2022;Petts, Carlson, and Pepin 2021;Umamaheswar and Tan 2020). Disruptions to the social order (e.g., disruption of basic services) posed by disasters more generally tend to make gendered power relations more salient (Enarson 2012;Enarson and Scanlon 1999).…”
Section: The Gendered Division Of Household Labor During the Pandemicmentioning
confidence: 99%
“…Throughout the pandemic, immigrant populations faced additional stressors, including fear of deportation, limited access to crucial social services, such as healthcare, ineligibility for national unemployment benefits, and exclusion from government relief packages ( Wilson and Stimpson, 2020 ). The closure of schools and daycares further exacerbated gender inequalities in both paid and unpaid labor, as immigrant women took on more housework and childcare responsibilities at home ( Haney and Barber, 2022 ). Balancing family and work became increasingly challenging, given the limited employment opportunities, financial strain, growing family responsibilities, and uncertainty arising from the suspension of services related to legal status ( Trentin et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%